2011
DOI: 10.1097/nen.0b013e3182358e4e
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NOX2 by the Stimulation of Ionotropic and Metabotropic Glutamate Receptors Contributes to Glutamate Neurotoxicity In Vivo Through the Production of Reactive Oxygen Species and Calpain Activation

Abstract: Prolonged activation of glutamate receptors leads to excitotoxicity. Several processes such as reactive oxygen species (ROS) production and activation of the calcium-dependent protease, calpain, contribute to glutamate-induced damage. It has been suggested that the ROS-producing enzyme, NADPH oxidase (NOX), plays a role in excitotoxicity. Studies have reported NOX activation after NMDA receptor stimulation during excitotoxic damage, but the role of non-NMDA and metabotropic receptors is unknown. We evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 90 publications
2
58
0
Order By: Relevance
“…S1). These findings agree with prior reports identifying NOX2 as the primary source of NMDA-induced superoxide production (13,14,(17)(18)(19), and they establish that both of the indicators Significance Activation of NMDA-type glutamate receptors produces neuronal excitotoxicity, a primary cause of cell death in stroke and other neurological disorders. This cell death process requires superoxide release by neuronal NADPH oxidase.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…S1). These findings agree with prior reports identifying NOX2 as the primary source of NMDA-induced superoxide production (13,14,(17)(18)(19), and they establish that both of the indicators Significance Activation of NMDA-type glutamate receptors produces neuronal excitotoxicity, a primary cause of cell death in stroke and other neurological disorders. This cell death process requires superoxide release by neuronal NADPH oxidase.…”
Section: Resultssupporting
confidence: 81%
“…Superoxide production by NADPH oxidase is a requisite event in the process leading from NMDA receptor activation to excitotoxic cell death (13)(14)(15)(16)(17)(18)(19) Together, the pH sensitivity of NOX2 and the role of NOX2 in NMDA receptor-mediated cell death suggest the possibility that reduced intracellular pH might limit neurotoxicity by dissociating NMDA receptor activation from superoxide production. Findings presented here confirm that both the superoxide production and cell death resulting from neuronal NMDA receptor activation are highly pH sensitive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…phox -/ -neurons, which cannot form a functional NOX2 complex, likewise show markedly attenuated superoxide formation and cell death in response to NMDA (17,60,65,150), and these are restored in p47 phox -/ -neurons transfected to express p47 phox (17,150). A third line of evidence arises from the specific requirement for glucose to fuel NADPH regeneration through the pentose phosphate pathway (45, 67).…”
Section: Fig 1 Nadph Oxidase (Nox)mentioning
confidence: 99%
“…We hypothesize that the NOX2 holoenzyme may be a major contributor of superoxide. NOX2 has long been associated with inflammatory processes (see for review (Sorce and Krause, 2009, Sareila et al, 2011)) and is found in both neurons and microglia (Guemez-Gamboa et al, 2011). Moreover, NOX2 is upregulated in microglia in spinal nerve transection models and its deletion attenuates the development of neuropathic pain and associated neuroimmune activation and oxidative stress in the spinal cord (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%